Initial biophysical characterization of Amynthas gracilis giant extracellular hemoglobin (HbAg) - Oliveira, J. B.S. [UNESP]; Ramos, L. [UNESP]; Souza, C. O. [UNESP]; Sebastião, I. [UNESP]; Caruso, C. [UNESP]; Carvalho, F. A.O.; Carvalho, J. W.P.; Morgante, P. G. [UNESP]; Santiago, P. S. [UNESP] (Springer Nature, 2020)
The aim of the present work was the biophysical characterization of the Amynthas gracilis hemoglobin (HbAg). The oxy-HbAg optical absorption data, with Soret and Q bands centered at 415, 540 and 575 nm, were stable and unchanged at pH 7.0. An increase in pH promotes decrease in the intensity in the optical absorption bands, suggesting an oligomeric dissociation and partial oxidation. Identical stability at pH 7.0 was observed in DLS results that presented a hydrodynamic diameter of 28 nm, characteristic of the whole oligomer. DLS shows that HbAg undergoes oligomeric dissociation and an aggregation/denaturation process that corroborates spectroscopic data. Our results showed that the monomer d presents four isoforms with molecular mass (MM) ranging from 16,244 to 16,855 Da; the trimer subunit presents two isoforms, (abc)1 and (abc)2, with MM of 51,415 ± 20 Da and 51,610 ± 14 Da, respectively, and a less intense species, at 67,793 Da, assigned to the tetramer abcd. Monomeric chains a, obtained from reduction of the disulfide-bonded trimer abc, present four isoforms with MM 17,015 Da, 17,061 Da, 17,138 Da and 17,259 Da. DLS and LSI revealed an isoeletric point (pI) of oxy-HbAg of 6.0 ± 0.3 and 5.5, respectively. Data analysis by IEF–SDS–PAGE revealed that the pI of oxy-HbAg is 6.11, correlating with DLS and LSI data. These studies indicate that oxy-HbAg is very stable, at pH 7.0, and has differing properties from orthologous giant hemoglobins.
Keywords: Biophysical characterization; Erythrocruorin; Hemoprotein; Oligomeric stability; Spectroscopy studies